Program Kemitraan Dan Bina Lingkungan Sebagai Bentuk Pemberdayaan Masyarakat Di Belawan Kota Medan - Simson Ginting (Jurnal Administrasi dan Kebijakan Publik, 2019)
The purpose of this research is to find out whether PT. (Persero) Indonesia's Port of Belawan Main Branch I have been doing local community empowerment activities (its environment) and what are the factors that hampered and supporters in the activities of the community empowerment. This research was qualitative research with a descriptive method, i.e. the research procedure that generates descriptive data in the form of the written word or spoken and the behavior of people who observed, i.e. the existing community around the the environment of PT Persero Indonesia's Port I main branch of Belawan, through interviews, observation and documentation. Community empowerment in the environs of PT. (Persero) Indonesia's Port I main branch of Belawan in partnerships program with small businesses and Community Development Program is still limited to venture capital lending, assistance towards victims of natural disasters, aid (contribution) of education, and public development assistance. This is more emphasize the economic and development dimensions rather than the social and science and technology dimensions. Obstacles faced was the lack of funds for the implementation of the community development program and partnership as well as a lack of field employee that is in charge of providing training and education for the built community. The surrounding community is not directly involved in policy making to support community empowerment activities. Likewise in solving problems by allowing problems to occur, without providing assistance for their resolution. Like when partner experience obstacles in repaying loan capital, they just bill to the place of the business partners. If it doesn't already exist, it will be billed the following month, without any assistance how to solve the problem.